Insights into Factors Impacting On Non-Communicable Diseases in the Prisons of Pakistan- A Scoping Review: Factors Impacting Non-Communicable Diseases in Pakistani Prisons - Shahzad, Tuba; Plugge, Emma; Van Hout, Marie Claire (Pakistan Journal of Health Sciences, 2024)
Non-Communicable Diseases (NCDs) continue to increase globally, including where recorded among prison populations. Pakistan, like many low- and middle-income countries is facing significant health system challenges. Little is known about NCDs in its prison population. A scoping review mapped and described what is known about factors impacting on NCDs in the prison population of Pakistan. Objective: To describe factors impacting Non-Communicable Diseases (NCDs) in the prison population of Pakistan and to inform policy and improve prison conditions, nutrition, and healthcare for effective NCD management and care. Methods: A comprehensive search was conducted on Web of Science, PubMed and EMBASE, restricted to publications from 2000 to 2023. Eight studies fulfilled the eligibility criteria. Records were independently screened, charted and content analysis was undertaken. Results: Six themes were generated; Nutritional and dietary provisions, Physical activity and body mass index; Substance use and dependence; Hypertension and diabetes; Access to medical care and Mental health. Prior and detention related risk and lifestyle factors underpin the chronic ill health of people living in prison. These include prior history of smoking and alcohol use, and situational aspects of prison conditions causing environmental stress, malnutrition and sedentarism. Where reported, hypertension, obesity and depression were high among people in prison. Conclusions: Prisons are fundamental to the domestic NCD response. Prisons in Pakistan require dedicated resourcing to improve basic conditions, nutrition and healthcare allocations for all people living in prisons. The review highlights the need for prison-based NCD screening, diagnosis, treatment and care in Pakistan, in close alliance with specialist care in hospitals. Further health research is warranted to examine the effectiveness of NCD policies and practices in place in contemporary prison systems in Pakistan.